Changes in Community Behavior in Congregational Prayers After the Pandemic: Perubahan Perilaku Masyarakat dalam Shalat Berjamaah setelah Pandemi - Iva Murida (IAIN Parepare, 2023)
The post-pandemic community phenomenon is a problem that occurs in the community in Katomporang Village. Changes in the community's congregational prayer behavior and the factors that cause changes in behavior in the community in Katomporang Village. This research aims to determine and analyze changes in worship behavior in society and the factors that cause changes in behavior in society. This research uses a descriptive qualitative method, namely the researcher identifies the situation in the field by conducting surveys, interviews and documentation, revealing the phenomena that occur. Meanwhile the approach is a phenomenological approach. The results of the research show that people experienced changes in behavior in carrying out worship activities such as congregational prayers, when the spread of the Covid-19 pandemic got worse until the PSBB regulations were implemented, people prayed with their families in their respective homes, congregational prayers were held at a distance, wearing masks, shaking hands between congregants after performing congregational prayers is prohibited. While the factors causing changes in behavior are that wearing a mask during the pandemic has become a recommendation or necessity for the public to avoid the Covid-19 outbreak, in normal times now masks have been used as a style accessory and can increase a person's self-confidence in public places. People at the peak of the pandemic were advised to provide distance in congregational prayers so that the habit persists to this day, so that the rows in congregational prayers at the mosque still provide distance and betweenness.